TRADISI MASYARAKAT SELO DAN PARIWISATA DI TAMAN NASIONAL GUNUNG MERBABU, BOYOLALI JAWA TENGAH - Indah Riadi Putri; Lies Rahayu Wijayanti Faida; Chafid Fandeli; Ris Hadi Purwanto (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2017)
Culture can form civilization or tradition in meeting the needs and well being of the people involved in the environment. One of form the human culture is a work of art. Artwork reveals the attitudes, processes, Symbolics meaning in the form of movement, carvings, paintings, material realized from social and cultural knowledge. Cultural attractions have a high appeal because it has a special value in the form of art performances, traditional ceremonies, the noble values that are contained in an object of man's work in the past. People have a variety of cultural art that consists of various traditions ceremonies, art performances, habits of indigenous people in life. It can be a potential cultural attraction for tourists who visit the National Park area of Mount Merbabu in District Selo, Boyolali regency. The purpose of this research is to know the traditions of performance, art, and culture the people of Selo, Merbabu Mountain National Park, Boyolali Central Java. Culture can shape civilization or tradition in the needs and welfare of life for the people involved in its environment. One form of human culture is the work of art, which reveals attitudes, processes, symbols of meaning in the form of movements, carvings, paintings, material embodied from social and cultural knowledge. Social and cultural knowledge embodies special things such as artistic attractions, traditional rituals passed down until to the present day. The meaning of this honor is an expression of gratitude to the spirit of the ancestors who have helped keep the balance of the region and the agriculture of the Selo community to be safe, safe and abundant. This research uses qualitative and quantitative analysis method by measuring distribution/frequency of performance and implementation of tradition/culture of Selo society. The Selo community has various artistic and traditional cultures, including art performances, ancestral honors (sadranan on the 1st night of Suro), clean villages, and thanksgiving for the harvest. The results of the study found that: 1) the tradition of traditional ceremonies in the form of homage to ancestral spirits (ancestors) of 7.1 percent, 2) performances sendratari of 54.52 percent, 3) the use of public buildings with local architecture of Java that serves as a gallery art as much as 59.03 percent, and 4) Community activities work together 75.48 percent. The data also indicates that the traditions and culture of the Selo community, not only as a potential support for tourism but become an integral part of the development of nature tourism in the area of Gunung Merbabu National Park Boyolali, Central Java.